Analisis Standar Pelayanan Minimal Untuk Rawat Inap dan Rawat Jalan di RSUD Pambalah Batung Amuntai Tahun 2012 - Dion Angger Priyatama; Aris Antoni; Khaiyatun Najiah; Stikes Husada Borneo; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2014)
Minimum standard service is provision of the type and quality of basic services which is a matter for obligated area that every entitled obtained minimum of citizen. That also represent the technical specification about measuring rod of minimum service given by public service body to society. To know the minimum standard service in RSUD Pambalah Batung Amuntai conducted by analysis about service give taking care of to lodge the underwriter doctor reply, availibility of service take care of to lodge the clock of visite doctor, death of patient > 48 Hours, occurence come home to force and to take care of outpatient is the availibility of service to take care it , Time to open the service to take care of outpatient , lay of time taken care outpatient , satisfaction of Costumer and straightening of diagnosed of TB through microscopic inspection TB.Research type used is descriptive by using interview, observation and document study to know the service standard take care of to lodge and take care outpatient in RSUD Pambalah Batung Amuntai. this Sampel Research is service take care of to lodge, service take care of outpatient and patient. this Data presentation in form of tekstular. Pursuant to result of research of service type take care of the service take care of to lodge which not yet fulfilled the time of standard visite doctor and for the service of take care of outpatient which not yet fulfilled the minimum service standard is giving service to outpatient open time of the service and the time of took care wait. the Service type not yet fulfilled the standard because lack of specialist doctor and lack of registration worker in RSUD Pambalah Batung Amuntai.